Blended Learning in Indian Colleges with Massively Empowered Classroom - Cutrell, Ed; O'Neill, Jacki; Bala, Srinath; Nitish, B.; Cross, Andrew; Kumar, Viraj; Thies, Bill (ACM - Association for Computing Machinery, 2015)
Students in the developing world are frequently cited as being among the most important beneficiaries of online education initiatives such as massive open online courses (MOOCs). While some predict that online classrooms will replace physical classrooms, our experience suggests that blending online and in-person instruction is more likely to succeed in developing regions. However, very little research has actually been done on the effects of online education or blended learning in these environments. In this paper we describe a blended learning initiative that combines videos from a large online course with peer-led sessions for undergraduate technical education in India. We performed a randomized controlled trial (RCT) that indicates our intervention was associated with a small but significant improvement in performance on a summative exam. We discuss the results of the RCT and an ethnographic study of the intervention to make recommendations for future, scalable blended learning initiatives for places such as India.